„Kiedy pada słowo rak, ludzie zaczynają mówić szeptem”. Społeczna historia raka w Polsce po 1945 roku - Szpak, Ewelina (Polska 1944/45-1989. Studia i Materiały, 2018)
Głównym celem prezentowanego artykułu jest odpowiedź na pytanie, jakie znaczenie w powojennej polityce zdrowotnej państwa i w społecznym postrzeganiu problemów zdrowotnych miały choroby nowotworowe. Jako choroby cywilizacyjne dotykające w coraz większym stopniu ludzi na całym świecie z uwagi na swą „tajemniczość” i wysoką śmiertelność, budziły z reguły wiele lęków i uprzedzeń. W jakim stopniu i formie lęki te dostrzegane były również w powojennym społeczeństwie polskim i jaki wpływ na ich występowanie miała polityka zdrowotna państwa (oświata i infrastruktura onkologiczna, programy rządowe) – to główne pytania, na które odpowiadam w tekście. “When the C-word is uttered, people began to whisper”. A social history of cancer in Poland after 1945 The main subject of research presented in the article are the ways of perceiving malicious tumour diseases by the society, medical community and the state authorities responsible for the health protection policy. The text brings up both the questions of registering and increasing cancer rates, and changing attitude of Polish people to oncologic care. On the basis of archival sources, both the press articles and narrative texts, the author outlines problems with the oncology education, extremely limited before the 1970s, and with popular social belief (and fears) related to cancerous diseases. An important element of the analyses are also limitations of the public health infrastructure of the contemporary People’s Poland and lines of the so-called “cancer policy” defined in the form of Governmental Programme against Cancerous Diseased (PR6) launched in 1976.